Pulmonary artery and left heart end-diastolic pressure relations. Issue 6 (November 1970) - Herbert, W H
Abstract : The exponential fall of the pulmonary pressure curve from its systolic peak to left atrial pressure previously described in the presence of normal intraventricular conduction has been investigated in patients with right bundle-branch block. We have been able to show once more that the pulmonary artery diastolic pressure seeks the left atrial level: when right ventricular systole is delayed the pulmonary artery pressure continues to fall with the left atrial 'x' descent.